2003
DOI: 10.1243/095440703322114988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tumble and swirl flows on turbulence scale near top dead centre in a four-valve spark ignition engine

Abstract: The in-cylinder ow eld and the turbulence scale at the ignition timing play an important role in enhancing the propagation speed of the initial ame and the engine combustion. The aim of this work is to investigate the e ect of tumble and swirl ows on the turbulence scale near the top dead centre in a four-valve spark ignition (SI ) engine by an experimental method. In this study, various ow elds such as tumble and swirl ows were generated by intake ow control valves. For investigation of the ow elds, the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Fig.9. Turbulence intensity variations at different positions for the two intake ports [39] Recently, a combined swirl and tumble flows have been used in both SI and CI engines [22, [41][42][43][44]. Floch et al [22] analyzed the effect of tumble and swirl on turbulence and combustion by means of flow-control baffle placed between the intake manifold and the cylinder head.…”
Section: Tumble Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig.9. Turbulence intensity variations at different positions for the two intake ports [39] Recently, a combined swirl and tumble flows have been used in both SI and CI engines [22, [41][42][43][44]. Floch et al [22] analyzed the effect of tumble and swirl on turbulence and combustion by means of flow-control baffle placed between the intake manifold and the cylinder head.…”
Section: Tumble Flowmentioning
confidence: 99%
“…They pointed that tumble generated greater turbulence in the combustion chamber than swirl at an identical angular momentum measured in the steady flow test. Likewise, Lee et al [42] analyzed the effects of tumble and swirl flows produced a swirlintensifying valve (SIV) and a tumble intensifying-valve (TIV) on the turbulence scale by using the single-frame PTV and the twocolor PIV during the intake and compression processes in SI engine. It is found that the TIV generated larger tumble ratio and so turbulent intensity than SIV near the spark timing and the flame propagation speed increased in swirl and tumble flow fields with a lean air-fuel ratio.…”
Section: Tumble Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [20] experimentally studied the effect of the tumble and the swirl flows on the turbulence near TDC for correlating the flow field generated in the intake stroke with the turbulence intensity near the spark timing. In Achuth et al [21] it was highlighted as the tumble breakdown and the consequent turbulence are affected by the chamber shape: for the same piston, they depend on the head shape and in particular on the pentroof angle.…”
Section: Literature Summary On the Tumble Motionmentioning
confidence: 99%
“…Mas recientemente se usa anemometría láser Dopler (LDA) (Kang y Reitz, 2000;Hong y Tarng, 2001), velocimetría del rastro de partículas (PTV) (Lee et al, 2001) y velocimetría de la imagen de partículas (PIV) (Lee y Lee, 2003;Lee et al, 2005;Yasar, 2006).…”
Section: Introductionunclassified